A Randomized, Double-Blind, Parallel-Controlled Phase I Study Comparing the Pharmacokinetics, Safety, and Immunogenicity of SCT510 to Bevacizumab (Avastin®) in Healthy Chinese Males - Jing Wu; Guolan Wu; Liangzhi Xie; Duo Lv; Chang Xu; Huili Zhou; Lihua Wu; Jingjing Zhang; Jianzhong Shentu (Adis, Springer Healthcare, 2023)
Abstract Background SCT510 is a recombinant humanized monoclonal antibody targeting vascular endothelial growth factor (VEGF), which is intended as a candidate biosimilar of bevacizumab that is approved for various metastatic cancers.Please confirm change in wording to match definition for VEGF belowYes. Objective This study aimed to compare the pharmacokinetics profiles, safety, and immunogenicity of SCT510 to bevacizumab (Avastin®) in healthy Chinese males. Methods This was a single-center, double-blind, parallel-group phase I study. A total of 84 participants were randomly assigned (1:1) to receive a single 3 mg/kg infusion of either SCT510 or bevacizumab and followed up for 99 days. Primary endpoints were area under the serum concentration-time curve from time 0 extrapolated to infinity (AUC0-∞), area under the serum concentration-time curve from time 0 to last quantifiable concentration (AUC0-t), and the maximum observed concentration (Cmax). Secondary endpoints included safety and immunogenicity.Kindly check and confirm the edit made in the article title.Yes. Results A total of 82 subjects completed the study. Geometric means ratios (GMR) for AUC0-∞, AUC0-t, and Cmax were 0.88, 0.89, and 0.97, respectively, for SCT510 versus bevacizumab (USA). The 90% confidence intervals for GMRs of AUC0-∞, AUC0-t, and Cmax were all within the prespecified criteria (80-125%). No adverse events (AEs) led to study termination, and no serious adverse events (SAEs) were reported. None of the anti-drug antibodies (ADAs) identified were found to be neutralizing antibodies (NAbs), and only one subject from the SCT510 group tested positive for the ADA at the day 99 visit. Conclusion This study demonstrated that the pharmacokinetics, safety, and immunogenicity of SCT510 were equivalent to bevacizumab (Avastin®). As a proposed biosimilar drug to bevacizumab, SCT510 was well tolerated in healthy Chinese males. Clinical Trials Registration NCT05113511.